Spontaneous Formation of Prebiotic Compartment Colonies on Hadean Earth and Pre‐Noachian Mars. Issue 3 (11th February 2022) - Köksal, Elif S.; Põldsalu, Inga; Friis, Henrik; Mojzsis, Stephen J.; Bizzarro, Martin; Gözen, Irep
Abstract: Prominent among the models for protocells is the spherical biosurfactant shell, freely suspended in aqueous media. This model explains initial, but not subsequent events in the development process towards structured protocells. Taking into consideration the involvement of naturally occurring surfaces, which were abundant on the early Earth, feasible and productive pathways for the development of primitive cells are reported. Surfaces intrinsically possess energy, easily utilized by the interfacing amphiphiles, such as lipids, to attain self‐organization and spontaneous transformations. This work shows that the physical interaction of phospholipid pools with 20 Hadean Earth analogue materials as well as a Martian meteorite composed of fused regolith representing the ancient crust of Mars consistently lead to the shape transformation and autonomous formation of surfactant compartment assemblies. Dense, colony‐like protocell populations grow from these lipid deposits, predominantly at the grain boundaries or cleavages of the investigated natural surfaces, and remain there for several days. The model protocells in this study are able to autonomously develop, transform and pseudo‐divide, and encapsulate RNA as well as DNA. Moreover, they can accommodate non‐enzymatic, DNA strand displacement reactions. These findings suggest a feasible route towards the transformation from non‐living to living entities, and provide fresh support for the 'Lipid World' hypothesis. Abstract : Autonomous formation of primitive cell‐like compartment populations is observed on thin sections of early Earth minerals and a Martian meteorite specimen. Multilamellar lipid reservoirs undergo a series of autonomous shape transformations, resulting in formation of networks of lipid compartments or compartment aggregates resembling microbial colonies. The compartments are able to encapsulate RNA and accomodate non‐enzymatic entropy‐driven DNA reactions.